Altered gut fungi in systemic lupus erythematosus – A pilot study - Li, Bao-Zhu; Wang, Hua; Li, Xian-Bao; Zhang, Qian-Ru; Huang, Rong-Gui; Wu, Hong; Wang, Yi-Yu; Li, Kai-Di; Chu, Xiu-Jie; Cao, Nv-Wei; Zhou, Hao-Yue; Fang, Xin-Yu; et al. (Frontiers in Microbiology, 2022)
Objective Gut fungi, as symbiosis with the human gastrointestinal tract, may regulate physiology via multiple interactions with host cells. The plausible role of fungi in systemic lupus erythematosus (SLE) is far from clear and need to be explored. Methods A total of 64 subjects were recruited, including SLE, rheumatoid arthritis (RA), undifferentiated connective tissue diseases (UCTDs) patients and healthy controls (HCs). Fecal samples of subjects were collected. Gut fungi and bacteria were detected by ITS sequencing and 16S rRNA gene sequencing, respectively. Alpha and beta diversities of microbiota were analyzed. Linear discriminant analysis effect size analysis was performed to identify abundance of microbiota in different groups. The correlation network between bacterial and fungal microbiota was analyzed based on Spearman correlation. Results Gut fungal diversity and community composition exhibited significant shifts in SLE compared with UCTDs, RA and HCs. Compared with HCs, the alpha and beta diversities of fungal microbiota decreased in SLE patients. According to principal coordinates analysis results, the constitution of fungal microbiota from SLE, RA, UCTDs patients and HCs exhibited distinct differences with a clear separation between fungal microbiota. There was dysbiosis in the compositions of fungal and bacterial microbiota in the SLE patients, compared to HCs. Pezizales, Cantharellales and Pseudaleuria were enriched in SLE compared with HCs, RA and UCTDs. There was a complex relationship network between bacterial and fungal microbiota, especially Candida which was related to a variety of bacteria. Conclusion This study presents a pilot analysis of fungal microbiota with diversity and composition in SLE, and identifies several gut fungi with different abundance patterns taxa among SLE, RA, UCTDs and HCs. Furthermore, the gut bacterial-fungal association network in SLE patients was altered compared with HCs.